A MUSCOVITE PRINCE IN KHAN UZBEK’S CAMPAIGN: RECONSTRUCTING YURI DANILOVICH’S SOJOURN IN THE HORDE - Seleznev, Urij Vasil'evic (History, Archeology and Ethnography of the Caucasus, 2025)
The presence of Russian princes and their retinues at Khan Uzbek’s headquarters during the winter of 1318–1319 remains unresolved. However, an examination of contemporaneous events indicates that, at that time, the Horde’s forces were engaged in a campaign in Transcaucasia. Indirect evidence suggests that the retinues from the appanage principalities of the Grand Principality of Vladimir had assembled at the Horde ruler’s headquarters, including the warriors of the executed Prince Mikhail Yaroslavich of Tver, commanded by his twelve-year-old son, Konstantin. This concentration of military units can be attributed to strategic military necessities. Consequently, it is plausible that the forces of the Grand Principality of Vladimir, under the leadership of the grand prince, Yuri Danilovich of Moscow, participated in Uzbek’s Transcaucasian campaign, engaged in combat operations, and incurred losses. Horde troops, potentially incorporating Russian retinues, clashed at the crossings of the Kura River and sustained casualties during the retreat through Derbent. It is highly probable that Prince Yuri’s ally and patron, the noyon/emir Kavgadyi, perished in these engagements. Moreover, Arabic sources from the East document the presence of Russian units at Khan Uzbek’s headquarters in 1318–1319. The alignment of the timeline for the Vladimir forces’ stay at the khan’s headquarters with these source accounts enables us to equate Yuri Danilovich’s troops with the “host of Circassians, Russians, and Jasz.” A thorough synthesis of the available direct and indirect evidence allows for a tentative reconstruction of the chronology of Russian troops’ involvement in Khan Uzbek’s Transcaucasian campaign.
Keywords: Derbent; Yuri Danilovich; Uzbek; Hulagu; Kura; Golden Horde; Ilkhanate; Kavgadyi